1994
DOI: 10.1113/jphysiol.1994.sp020135
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation mechanisms induced by stimulation of nerves and by nitric oxide in sheep urethral muscle.

Abstract: 1. Isolated transverse and longitudinally oriented preparations of sheep urethra precontracted with noradrenaline responded to electrical field stimulation (EFS) with stimulus-dependent non-adrenergic, non-cholinergic (NANC) relaxations. 2. Exogenous nitric oxide (NO) (acidified NaNO2), S-nitroso-L-cysteine (NC), sodium nitroprusside (SNP), 8-Br-cGMP, dibutyryl-cAMP, forskolin and isoprenaline each relaxed precontracted transverse urethral preparations in a concentration-dependent manner in order of potency: N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
(38 reference statements)
9
30
0
Order By: Relevance
“…This observation supports the above view, since oxyhaemoglobin evokes its inhibitory action by binding NO-directly to form a nitrosyl-haemoprotein complex which prevents the diffusion of NO-from nerve terminals to smooth muscle cells (Martin, Villani, Jothianandan & Furchgott, 1985). Furthermore, Methylene Blue which has previously been proposed as a specific inhibitor of soluble guanylate cyclase (Martin et al 1985), has recently been suggested to inactivate NO-by generation of the superoxide anion (02-) (Garcia-Pascual & Triguero, 1994). It has been shown that a reduced form of Methylene Blue can generate the superoxide anion by auto-oxidation in the presence of oxygen (MacCord & Fridorich, 1970) and that NO-can be inactivated by the superoxide anion (Palmer, Ferrige & Moncada, 1987 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports the above view, since oxyhaemoglobin evokes its inhibitory action by binding NO-directly to form a nitrosyl-haemoprotein complex which prevents the diffusion of NO-from nerve terminals to smooth muscle cells (Martin, Villani, Jothianandan & Furchgott, 1985). Furthermore, Methylene Blue which has previously been proposed as a specific inhibitor of soluble guanylate cyclase (Martin et al 1985), has recently been suggested to inactivate NO-by generation of the superoxide anion (02-) (Garcia-Pascual & Triguero, 1994). It has been shown that a reduced form of Methylene Blue can generate the superoxide anion by auto-oxidation in the presence of oxygen (MacCord & Fridorich, 1970) and that NO-can be inactivated by the superoxide anion (Palmer, Ferrige & Moncada, 1987 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that NC effectively induced cyclic GMP accumulation in oviductal vascular preparations argues against MB being a specific inhibitor of soluble guanylate cyclase as is generally assumed. Generation of 02-, which induces direct chemical inactivation of extracellular NO has been shown to mediate the inhibition of NO-dependent relaxations by MB in some tissues (Wolin et al, 1990;Garcia-Pascual & Triguero, 1994). Nitrosothiols, such as NC can yield NO directly to the cytoplasm of smooth muscle cells following denitrosation at the membrane (Kowaluk & Fung, 1990), being less sensitive to extracellular inactivation by 02-.…”
Section: I1-mentioning
confidence: 99%
“…The analytical procedure followed is described elsewhere (Garcia-Pascual & Triguero, 1994) with minor modifications. In brief, vessel segments were quickly plunged into liquid nitrogen and stored at -70'C.…”
Section: Determination Of Cyclic Gmp Levelsmentioning
confidence: 99%
“…A rich supply of nitrergic nerves has been identified by NADPH-diaphorase histochemistry and nitric oxide synthase (NOS) immunohistochemistry in the outflow region (urethra, bladder neck and bladder base or trigone) of several species including rat (McNeill et al, 1992), pig (Persson et al, 1993), sheep (Triguero et al, 1993) and human (Smet et al, 1994a;Leone et al, 1994). Furthermore, functional studies have demonstrated that isolated urethral and trigonal smooth muscles in all the species studied so far, respond to electrical field stimulation (EFS) with pronounced NANC relaxations, which can be blocked by NO synthesis inhibitors and mimicked by NO and NO donors (Garcia-Pascual et al, 1991;Andersson et al, 1991;Persson et al, 1992;1993;Garcia-Pascual & Triguero, 1994). This suggests that NO, or a related compound, is the relaxant mediator, which acts by increasing guanosine 3':5'-cyclic monophosphate (cyclic GMP) levels in smooth muscle (Garcia-Pascual & Triguero, 1994;Dokita et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, functional studies have demonstrated that isolated urethral and trigonal smooth muscles in all the species studied so far, respond to electrical field stimulation (EFS) with pronounced NANC relaxations, which can be blocked by NO synthesis inhibitors and mimicked by NO and NO donors (Garcia-Pascual et al, 1991;Andersson et al, 1991;Persson et al, 1992;1993;Garcia-Pascual & Triguero, 1994). This suggests that NO, or a related compound, is the relaxant mediator, which acts by increasing guanosine 3':5'-cyclic monophosphate (cyclic GMP) levels in smooth muscle (Garcia-Pascual & Triguero, 1994;Dokita et al, 1994). Moreover, an increase in both nitrite and nitrate, the metabolites of NO, has been measured in human urethral preparations upon EFS, which was inhibited by N0-nitro-L-arginine methyl ester (L-NAME) (Leone et al, 1994).…”
mentioning
confidence: 99%